Cavity‐filling dolomite speleothems and submarine cements in the Ediacaran Dengying microbialites, South China: Responses to high‐frequency sea‐level fluctuations in an 'aragonite–dolomite sea'. Issue 6 (1st July 2019) - Ding, Yi; Chen, Daizhao; Zhou, Xiqiang; Guo, Chuan; Huang, Taiyu; Zhang, Gongjing
Abstract: Speleothems, mostly composed of calcium carbonate, are widely present in modern karst‐originated caves, but have rarely been reported in palaeokarst systems. This study presents a novel type of dolomite speleothem and subsequent submarine dolomite cement, which are widely present in the upper Ediacaran Dengying Formation in the upper Yangtze area. These precipitated materials occur in the cavity system that cuts across several peritidal cycles. The interconnected cavity networks with irregular shapes, embayed walls, internal breccias on cavity floor and their preferential development in the shallower cycle tops (for example, tepee‐deformed beds) suggest that they were initially generated by subaerial dissolution. As the earliest infills, the hemispherical protrusions, icicle‐like pendants and ground‐up columns show similar morphological features and occurrence patterns to the cave popcorn, stalactites and stalagmites, respectively. Thus, these earliest infills are speleothems resulting from associated meteoric precipitation during subaerial exposure. The isopachous growth pattern of subsequent more extensive fibrous dolomite cements points to a submarine diagenetic environment in which they were precipitated. Microscopically, the micritic to micro‐crystalline dolomite, acicular dolomite in speleothems and the subsequent fibrous dolomite share similar crystal fabrics to metastable precursors (for example, Mg‐calcite). Meanwhile, the carbon‐oxygen isotope compositions of the speleothem and fibrous dolomite, although partly altered by burial diagenesis, share a large overlap with host rock and coeval marine carbonates all over the Yangtze Platform. For these reasons, these speleothems and fibrous cements are considered to have been initially precipitated as metastable carbonate precursors in meteoric and submarine environments, respectively, and stabilized during submarine mimetic dolomitization. The cyclic occurrence of cavity systems filled with speleothems and submarine cements reflects periodic subaerial exposure and marine flooding of broad tidal flat in the upper Yangtze area, driven by high‐frequency sea‐level fluctuations. Furthermore, the Neoproterozoic seawater chemistry that favoured early dolomitization of carbonate precursor mineralogies was an advantage for the preservation of fabrics from metastable precursor minerals.